Analysis of spatial and temporal characteristics of carbon emission efficiency of pig farming and the influencing factors in China - Guo, Hongpeng; Li, Shi; Pan, Chulin; Xu, Shuang; Lei, Qingyong (Frontiers in Public Health, 2023)
Pig production makes an important contribution to China's food security, but the intestinal fermentation and excretion of pig farming is an important source of greenhouse gas emissions. The study of pig farming carbon emission efficiency and influencing factors is an important issue to mitigate the impact of pig farming on environmental pollution. In this paper, we measured the carbon emission efficiency of pig farming in 30 provinces (autonomous regions and municipalities) from 2010 to 2020 by using the non-expected output SBM model and analyzed the spatial and temporal characteristics of the carbon emission efficiency of pig farming in China, and examined and analyzed the factors influencing the carbon emission efficiency of pig farming by using the limited dependent variable model (Tobit). The results show that: the carbon emission efficiency of pig farming in China shows an M-shaped upward trend in time sequence by comparing the carbon emission efficiency during the study period; the carbon emission efficiency of pig farming shows a decreasing trend in the east, middle and west regions of China by comparing the carbon emission efficiency of different regions horizontally, and the very low efficiency and low efficiency regions cluster from the east to the middle and west regions; the middle and high efficiency regions cluster in the east. The spatial characteristics of the very low efficiency and low efficiency areas cluster from the east to the central and western parts of China, and the medium and high efficiency areas cluster in the east. The regression analysis of the factors influencing the carbon emission efficiency of pig breeding shows that the comparative advantage of pig industry and transportation accessibility are positively correlated with the carbon emission efficiency of pig breeding, which improves the carbon emission efficiency of pig breeding; the proportion of food resources and market scale are negatively correlated with the carbon emission efficiency of pig breeding, which suppresses the carbon emission efficiency of pig breeding; the production layout index has no significant influence on the carbon emission efficiency of pig breeding.